2022
DOI: 10.1093/mnras/stab3786
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of barred galaxies in the EAGLE simulations

Abstract: We study the morphologies of 3,964 galaxies and their progenitors with M⋆ > 1010M⊙ in the reference eagle hydrodynamical simulation from redshifts z = 1 to z = 0, concentrating on the redshift evolution of the bar fraction. We apply two convolutional neural networks (CNNs) to classify 35,082 synthetic g-band images across 10 snapshots in redshift. We identify galaxies as either barred or unbarred, while also classifying each sample into one of four morphological types: elliptical (E), lenticular (S0), s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 166 publications
0
15
0
Order By: Relevance
“…Almost all the previous studies done in classification of galaxies are done to classify galaxies into at most 5 classes (Walmsley et al 2020) (Mittal et al 2020) (Jiménez et al 2020) (Eassa et al 2021) (Bom et al 2021) (Cavanagh et al 2021). But considering the development in theoretical aspects, we found that there was need of classifying it into more classes.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Almost all the previous studies done in classification of galaxies are done to classify galaxies into at most 5 classes (Walmsley et al 2020) (Mittal et al 2020) (Jiménez et al 2020) (Eassa et al 2021) (Bom et al 2021) (Cavanagh et al 2021). But considering the development in theoretical aspects, we found that there was need of classifying it into more classes.…”
Section: Resultsmentioning
confidence: 81%
“…spiral and elliptical. (Cavanagh et al 2021) have proposed 4 different models for classifying data into 2 (elliptical and spiral), 3 (elliptical, spiral and lenticular)and 4 (elliptical, spiral, lenticular and others) classes respectively. Due to limitation of data, the authors have rotated and flipped the images to generate additional data images.…”
Section: Related Workmentioning
confidence: 99%
“…C1). Given that these models are for bulge-dominated S0s, these results indicates that bar formation due to spontaneous bar instability and tidal interaction is unlikely in S0s thus provides a physical reason why the bar fraction in S0s is small both in observational studies and in cosmological simulations (e.g., Cavanagh et al 2022 for recent discussion on this topic). It can be seen clearly, however, that the orbital eccentricities of stars (e) in the tidal model become significantly higher: local APS do not work to form seed bars though.…”
Section: Appendix C: ωPre − E Maps In Other Modelsmentioning
confidence: 86%
“…In this paper, we do not discuss other key issues related to bar formation and evolution, such as dynamical interaction between bars and dark matter halos (e.g., Weinberg 1985;Debattista & Sellwood 2000). and redshift evolution of bars (e.g., Abraham et al 1999;Jogee et al 2004;Sheth et al 2008;Cavanagh et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In any case, this component emerges out of our analysis even if we assume a more restrictive criteria to exclude barred galaxies. However, the fact that the galaxies in our sample do not have a bar now does not necessarily imply they never had one, as it is still an open question whether bars are transient features (Bournaud & Combes 2002;Peschken & Łokas 2018;Cavanagh et al 2022) or not (Athanassoula 2005;Athanassoula et al 2013;Kim et al 2016). To clarify the nature of the spheroids in these EAGLE galaxies, we have to constrain how these components formed, an analysis which we leave for future work.…”
Section: Summary and Discussionmentioning
confidence: 97%